Global Harmonization through Restoration of Feminine Power (Proceedings of the International Conference on Future of Women, 2019)
The future of women is the same as our past and present global state of women as well as human kind. The notion of “this is a man’s world” has dictated so much of the Earths energy that it has often seeped down into our inner voices and thoughts destroying our natural balance. A restoration of feminine power is the greatest most pivotal balance act towards the Global Harmonization of the Human Race. She who creates life, gives life, and nurtures life has a great power and understanding to protect life as well as undoubtedly having the right to participate in how the collective life of the human race exists and precedes as well as her own. Female domination is not the goal. Simply, global harmony is the end game. Restoration of feminine power has the potential to heal and liberate our men and women cross culturally and intersectionally in every aspect through which we suffer while simultaneously strengthening the connection of all creatures whom we share the Earth with further alleviating environmental issues. The future of women is the future of the human race and our last option is our only option yet tried- global harmony.
Keywords: Global Harmony; Feminine Power; Witch-hunt; Revolution